CBRM Scaling and Networking Community Forum - Leinga, George; Notere Boso, Delvene; Saeni-Oeta, Janet; Siota, Faye Aborina; Kuma, Alafina; Sukulu, Meshach; Pua'ara, S (WorldFish, 2024)
Scaling up community-based resource management (CBRM) in Pacific Island countries is a regional priority for sustainable development and food security. A forum with community members, provincial fisheries officers, Ministry of Fisheries and Marine Resources’ CBRM Section officers and several national and regional partners working with CBRM discussed experiences and summarized lessons to support programs for national scaling up in Solomon Islands. Discussions from the forum sessions are summarized in this brief together with five highlighted lessons emerging from the discussions.